قرآن اور ما بعد الطبیعی نفسیات: نفسیاتی بحران، مادیت، اور اسلامی روحانیت کا تجزیاتی مطالعہ: THE QUR'AN AND METAPHYSICAL PSYCHOLOGY: AN ANALYTICAL STUDY OF PSYCHOLOGICAL CRISIS, MATERIALISM, AND ISLAMIC SPIRITUALITY (Al-Aasar, 2025)
Modern man is suffering from a severe psychological crisis characterized by anxiety, restlessness, and a sense of meaninglessness. The primary causes of this crisis lie in the dominance of materialistic thought, alienation from spirituality, and the reductionist approach of modern psychology which is primarily based on empirical and physical observations. This study presents an analytical examination of Metaphysical Psychology in the light of the Qur'an, aiming to reveal that the root causes of psychological disorders are not merely physical or neurological but are deeply connected to spiritual and metaphysical dimensions of the human self.The Qur'an describes the reality of the human being through concepts such as Nafs (Self), Ruh (Soul), and Qalb (Heart), which are not confined to biological or animalistic interpretations but represent higher metaphysical realities. This research demonstrates that the Qur'anic perspective identifies the spiritual causes of psychological issues such as anxiety, fear, despair, and existential emptiness, and offers remedies through Tawheed (Oneness of God), Dhikr (Remembrance of God), Sabr (Patience), Tawakkul (Reliance on God), and awareness of the Hereafter.Whereas Western materialistic psychology often confines human nature to brain chemistry, neural impulses, or unconscious drives, the Qur'an offers a spiritual psychology centered on restoring inner peace and existential meaning as part of the human being’s innate need. Within this framework, Islamic spirituality and Qur'anic teachings are presented as effective alternatives for addressing the modern psychological crisis.This paper concludes that Islamic spirituality not only provides healing from psychological disturbances but also guides man towards recognizing his purpose of existence, his cosmic connection, and his relationship with the Divine, leading to a balanced, peaceful, and spiritually resilient life.